Governance Gaps in the Rempang Eco-City Policy: Between Legal Authority and Social Legitimacy - Eva Amalia; Wahjoe Pangestoeti; Roni Adi; Siti Arieta (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2026)
This study examines the legality–legitimacy gap in the implementation of the Rempang Eco-City policy in Batam, Indonesia. The project is formally positioned as a strategic development agenda intended to accelerate investment, industrial expansion, tourism growth, and regional economic transformation. However, its implementation has generated significant social resistance among affected communities, particularly due to relocation plans, uncertainty over land tenure, disruption of fishing-based livelihoods, and threats to socio-cultural continuity. This research uses a qualitative descriptive-analytical method supported by library research and document analysis. Secondary data were obtained from statutory regulations, government documents, institutional reports, scholarly publications, public statements, and media sources related to Rempang Eco-City. Data were analyzed through a gap analysis model by comparing two main dimensions: formal legality, represented by legal basis, institutional authority, administrative procedures, and policy instruments; and social legitimacy, represented by public acceptance, participation quality, perceived fairness, and recognition of local rights. The findings show that although the Rempang Eco-City policy has a strong formal legal foundation, its implementation remains socially contested because affected communities perceive the process as top-down, insufficiently participatory, and inadequately responsive to their livelihood and cultural attachments. The study also finds that institutional fragmentation, weak deliberative governance, limited transparency, and relocation uncertainty intensify public distrust. Therefore, the Rempang case demonstrates that legal validity alone cannot guarantee policy acceptance or implementation sustainability. The study concludes that strategic development projects require inclusive governance, meaningful participation, accountable institutional coordination, and substantive relocation justice to transform formal legality into social legitimacy.